ChemInform Abstract: Reactions of 3‐Phenyl‐1, 2, 4‐triazine with Some C‐Nucleophiles. Issue 12 (25th March 2014) - Azev, Yurii A.; Ermakova, Ol'ga S.; Kodess, Mikhail I.; Ezhikova, Marina A.; Kovalev, Igor S.; Bakulev, Vasiliy A.
Abstract The reaction of triazine (I) with C‐nucleophiles (II) and (IV) is reported.